Thermal and Mechanical Properties of Epoxy Resin Functionalized Copper and Graphene Hybrids using In-situ Polymerization Method - Ali, Nadia A.; Abd-Elnaiem, Alaa M.; Hussein, Seenaa I.; Khalil, Asmaa S.; Alamri, Hatem R.; Assaedi, Hasan S. (Current Nanoscience, 2021)
Objective: In this work, graphene (Gr) or/and Cu particles are used to improve the thermal and mechanical properties of epoxy resin. Methods: Various contents of Gr powder (0.1, 0.3, and 0.5 wt%), and Cu powder (10, 30, and 50 wt%) were loaded to epoxy to form Gr/epoxy and Cu/epoxy composites, respectively. In addition, hybrids epoxy/Cu/Gr samples were prepared with a selection of the lowest (0.1 and 10) and the highest (0.5 and 50) ratios of Gr, and Cu, respectively. Results: The thermal conductivity increased with the increasing weight ratio of Gr and Cu as compared to the pure epoxy. The thermogravimetric analysis (TGA) of epoxy composites and hybrid composites revealed an improvement in the thermal stability. In addition, the mechanical properties such as hardness shore D and the wear resistance were enhanced for both the epoxy composites and hybrids composites. However, the Ep+0.5wt%Gr+50wt%Cu hybrid composite was found to have the maximum hardness 84, with the thermal conductivity of 3.84 W/m.K. It showed the lowest wear resistance 2.70-6 mm3/Nm at loading 10 N. Conclusion: The hybrid composite containing 0.5wt%Gr and 50wt%Cu shows the maximum hardness and thermal conductivity, as well as the lowest wear resistance when compared to other composites. The physical properties of the hybrid composite can be controlled by the host blend, and hence the morphology, and interfacial characteristics.
Keywords: Epoxy